2015
DOI: 10.5604/17322693.1142717
|View full text |Cite
|
Sign up to set email alerts
|

The use of biodegradable polymers in design of cellular scaffolds

Abstract: The objective of this work was to demonstrate the usage of biodegradable polymers, made of calcium alginate and dibutyrylchitin, in the design of cellular scaffolds having broad application in reconstructive therapy (dentistry, orthopedics). To visualize cells seeded on calcium alginate and dibutyrylchitin polymers DAPI staining of fibroblasts nuclei was used. The cytotoxicity of the materials and microscopic evaluation of the viability of seeded cells was tested with a PKH 67 fluorescent dye. To assess the ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The non-toxic and biodegradable characteristics of chitosan have facilitated the development of absorbable materials that require no postoperative removal, which greatly reduces the suffering of patients and simplifies the surgical procedure. Therefore, chitosan has applications for clinical research and development [16]. …”
Section: Discussionmentioning
confidence: 99%
“…The non-toxic and biodegradable characteristics of chitosan have facilitated the development of absorbable materials that require no postoperative removal, which greatly reduces the suffering of patients and simplifies the surgical procedure. Therefore, chitosan has applications for clinical research and development [16]. …”
Section: Discussionmentioning
confidence: 99%
“…Orlowska J. et al demonstrated the usage of calcium alginate and dibutyrylchitin polymers in cell seeding. Evaluation of this material displays that it is able to facilitate cell adhesion and shows no toxicity [37].…”
Section: Current Study On Medical Applicationsmentioning
confidence: 99%
“…[5,6] Polymers may be designed to be either non-absorbable or biodegradable (resorbable) depending on the desired application. [7][8][9] Non-absorbable polymers are appealing for encapsulated cell therapy, where a polymer membrane is used to protect cells from the immune system. [10] The transplanted cells can, therefore, produce therapeutic molecules for extended periods of time.…”
Section: Introductionmentioning
confidence: 99%